Integration of Genetic and Cytogenetic Maps and Identification of Sex Chromosome in Garden Asparagus (Asparagus officinalis L.) - Moreno, Roberto; Castro, Patricia; Vrána, Jan; Kubaláková, Marie; Cápal, Petr; García, Verónica; Gil, Juan; Millán, Teresa; Doležel, Jaroslav (Frontiers in Plant Science, 2018)
A genetic linkage map of dioecious garden asparagus (Asparagus officinalis L., 2n=2x=20) was constructed using F1 population, simple sequence repeat (SSR) and single nucleotide polymorphism (SNP) markers. In total, 1376 SNPs and 27 SSRs were used for genetic mapping. Two resulting parental maps contained 907 and 678 markers spanning 1947 and 1814 cM, for female and male parent, respectively, over ten linkage groups representing ten haploid chromosomes of the species. With the aim to anchor the ten genetic linkage groups to individual chromosomes and develop a tool to facilitate genome analysis and gene cloning, we have optimized a protocol for flow cytometric chromosome analysis and sorting in asparagus. The analysis of DAPI-stained suspensions of intact mitotic chromosomes by flow cytometry resulted in histograms of relative fluorescence intensity (flow karyotypes) comprising eight major peaks. The analysis of chromosome morphology and localization of 5S and 45S rDNA by FISH on flow-sorted chromosomes, revealed that four chromosomes (IV, V, VI, VIII) could be discriminated and sorted. Seventy-two SSR markers were used to characterize chromosome content of individual peaks on the flow karyotype. Out of them, twenty-seven were included in the genetic linkage map and anchored genetic linkage groups to chromosomes. The sex determining locus was located on LG5, which was associated with peak V representing a chromosome with 5S rDNA locus. The results obtained in this study will support asparagus improvement by facilitating targeted marker development and gene isolation using flow-sorted chromosomes.